2016
DOI: 10.1002/chem.201601634
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Oxazoles from Elusive Gold(I) α‐Oxocarbenes: A Mechanistic Study

Abstract: The gold(I) catalyzed reaction between phenylacetylene, pyridine N-oxide and acetonitrile leading, via a putative gold-α-oxocarbene intermediate, towards an oxazole product has been investigated. A novel mass spectrometric method called "delayed reactant labeling" is used to track consecutive and parallel reactions. It clearly shows that the intramolecular formation of a pyridine adduct of gold-α-oxocarbene is in competition with the formation of the oxazole product. The reaction mechanism most probably corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 109 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…10 Thus, among others, metal carbenes or carbenoids have been generated from α,β-unsaturated carbonyl compounds, 11 tosyl hydrazones, 12 triazoles, 13 cyclopropenes, 14 and propargyl ethers 15 or esters, 16 as well as from alkynes by oxidative processes. 17 However, highly stereoselective methods for the synthesis of vinylcyclopropanes that do not rely on the use of diazo reagents remain scarce. 18 In general, diastereopure vinylcyclopropanes are accessed in a stepwise manner through derivatization of functionalized cyclopropane building blocks, by either Wittig olefination 19 or metal-catalyzed cross-couplings.…”
Section: Introductionmentioning
confidence: 99%
“…10 Thus, among others, metal carbenes or carbenoids have been generated from α,β-unsaturated carbonyl compounds, 11 tosyl hydrazones, 12 triazoles, 13 cyclopropenes, 14 and propargyl ethers 15 or esters, 16 as well as from alkynes by oxidative processes. 17 However, highly stereoselective methods for the synthesis of vinylcyclopropanes that do not rely on the use of diazo reagents remain scarce. 18 In general, diastereopure vinylcyclopropanes are accessed in a stepwise manner through derivatization of functionalized cyclopropane building blocks, by either Wittig olefination 19 or metal-catalyzed cross-couplings.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the IRMPD spectra show that gold(I) α‐oxo carbenes cannot be isolated in the gas phase. Subsequent studies showed that the intermediates could not be isolated in the condensed phase either because they immediately couple with the leaving group of the oxidation reagent (for example pyridine from pyridine N ‐oxide) or with a solvent molecule …”
Section: Metal Complexesmentioning
confidence: 99%
“…We have developed a method -Delayed Reactant Labellingthat enables us to eliminate these artefacts and moreover to investigate the reaction kinetics of the ESI-MS detected ions in the reaction mixture. 12,23 Delayed Reactant Labelling consists of relative quantification of the detected signals with respect to their isotopically labelled analogues. Clearly, isotopically labelled intermediates cannot be just added to the reaction mixture, therefore we use a trick of adding an isotopically labelled reactant with a time delay to the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 These complexes can be then used as precatalysts by releasing the gold complex in the presence of an acid. 23,26 Gold-ketonyl complexes were also predicted as intermediates in a coupling reaction. 27 We have observed the formation of gold acetonyl complexes even in the absence of a base and could detect the signals of the monogold acetonyl as well as the digold acetonyl complexes.…”
Section: Introductionmentioning
confidence: 99%